2018
DOI: 10.1111/pbi.12987
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous CRISPR/Cas9‐mediated editing of cassava eIF4E isoforms nCBP‐1 and nCBP‐2 reduces cassava brown streak disease symptom severity and incidence

Abstract: Cassava brown streak disease (CBSD) is a major constraint on cassava yields in East and Central Africa and threatens production in West Africa. CBSD is caused by two species of positive-sense RNA viruses belonging to the family Potyviridae, genus Ipomovirus: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV). Diseases caused by the family Potyviridae require the interaction of viral genome-linked protein (VPg) and host eukaryotic translation initiation factor 4E (eIF4E) isoforms. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
157
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(163 citation statements)
references
References 95 publications
(130 reference statements)
2
157
0
4
Order By: Relevance
“…Genome editing of cassava was established using the CRISPR/ Cas9 technology for knocking out the Phytoene desaturase (MePDS) gene (Odipio et al, 2017). This technology was further utilized for developing cassava varieties with enhance resistance to the cassava brown streak disease (CBSD), caused by two species of Ipomovirus: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) (Gomez et al, 2018). CBSD is a major viral disease of cassava affecting its production in Central and East Africa.…”
Section: Improving Cassava Virus Resistance and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Genome editing of cassava was established using the CRISPR/ Cas9 technology for knocking out the Phytoene desaturase (MePDS) gene (Odipio et al, 2017). This technology was further utilized for developing cassava varieties with enhance resistance to the cassava brown streak disease (CBSD), caused by two species of Ipomovirus: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) (Gomez et al, 2018). CBSD is a major viral disease of cassava affecting its production in Central and East Africa.…”
Section: Improving Cassava Virus Resistance and Qualitymentioning
confidence: 99%
“…CBSD is a major viral disease of cassava affecting its production in Central and East Africa. Gomez et al (2018) reported that targeted mutations in cassava translation initiation factor 4E (eIF4E) isoforms nCBP-1 and nCBP-2 reduces CBSD disease severity as demonstrated with low degree of disease symptoms and virus accumulation in storage tuberous roots upon glasshouse challenge of edited cassava lines with CBSV. Simultaneous mutations in the nCBP-1 and nCBP-2 genes conferred significantly higher resistance to CBSD, however complete resistance to CBSD was not obtained in this study.…”
Section: Improving Cassava Virus Resistance and Qualitymentioning
confidence: 99%
“…In cassava, studies related to cloning and expression analysis of BE genes have been previously reported (Salehuzzaman et al 1992; Baguma et al 2003; Pei et al 2015). With the recent release of the cassava genome sequence (Prochnik et al 2012; Wang et al 2014; Bredeson et al 2016) and development of cassava transformation technology (Liu et al 2011; Zhang et al 2017), we now have the capacity to breed novel cassava cultivars with desirable traits using state‐of‐the‐art technologies including CRISPR/Cas9‐based genome editing (Odipio et al 2017; Sun et al 2017; Bull et al 2018; Gomez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Brown streak disease resistance [124] Citrus LOB1 Citrus canker resistance [125] Cucumber eIF4E Virus resistance [126] Flax EPSPS Herbicide resistance [95] Grape IdnDH Improvement of tartaric acid production [127] Oilseed rape…”
Section: Crispr/cas9 Systemmentioning
confidence: 99%